Konstruksi Wacana “Orang Desa Tidak Pakai Dolar” di Media Daring: Analisis Wacana Kritis van Dijk pada Detik.com, Tempo.co, dan Suara.com - Mahendra Senoaji (Universitas Widya Mataram, 2026)
This qualitative study aims to compare the discursive arrangements constructed by three Indonesian online media outlets with different ownership structures in their coverage of President Prabowo Subianto’s statement that villagers do not use U.S. dollars, delivered on May 16, 2026, amid the weakening of the Indonesian rupiah, which fell to Rp17,500 per U.S. dollar. The study applies Teun A. van Dijk’s critical discourse analysis across three dimensions text, social cognition, and social context to six news articles published between May 17 and 19, 2026, for which the full texts were accessible and could be verified. The findings show that all three media outlets incorporated both supportive and critical voices; therefore, their differences do not lie in the presence or absence of criticism, but rather in how discourse was arranged. Detik.com distributed the discourse across separate actor-based articles, employing intra-textual balancing through subheadings. Tempo.co concentrated the discourse within a single evaluative text, using a question-form headline and an argumentative structure that initially conceded before presenting a counterargument. Suara.com progressively accumulated technical evidence through a chain of narrative subheadings before placing official clarification in the closing position. This study proposes discursive arrangement as an analytical concept encompassing actor distribution, information sequencing, the positioning of balancing voices, and textual closure strategies, as an alternative to a simple pro-and-contra dichotomy. The findings are limited to the specific case examined and are not intended to constitute a quantitative comparison across media outlets. Keywords: Critical Discourse Analysis; Discursive Construction; Online Media; Discursive Arrangement; van Dijk.